Screening of Worldwide Barley Collection for Drought Tolerance: The Assessment of Various Physiological Measures as the Selection Criteria - Cai, Kangfeng; Chen, Xiaohui; Han, Zhigang; Wu, Xiaojian; Zhang, Shuo; Li, Qi; Nazir, Muhammad Mudassir; Zhang, Guoping; Zeng, Fanrong (Frontiers in Plant Science, 2020)
Drought is a devastating environmental constraint affecting the agronomic production of barley. To facilitate the breeding process, abundant germplasm resources and reliable evaluation systems to identify the true drought-tolerant barley genotypes are needed. In this study, 237 cultivated and 190 wild barley genotypes, originating from 28 countries, were screened for drought tolerance under the conditions of both water deficit and PEG-simulated drought at seedling stage. Drought stress significantly reduced the plant growth of all barley genotypes, but no significant difference in drought-induced reduction in the performance of barley seedlings was observed under these two drought conditions. Both cultivated and wild barley subspecies displayed considerable genotypic variability in drought tolerance, which underpinned the identification of 18 genotypes contrasting in drought tolerance. A comparative analysis of drought effects on biomass, water relation, photosynthesis and osmotic adjustment was undertaken using these contrasting barley genotypes, in order to verify the reliability of the screening and to obtain the credible traits as screening criteria of drought tolerance in barley. As expected, the selected drought-tolerant genotypes showed much less reduction in shoot biomass than drought-sensitive ones under water deficit, which was significantly positively correlated with the results of large-scale screening, confirming the reliability of the screening for drought tolerance under two drought conditions in this study. Likewise, the traits of water relation, photosynthetic activity and osmotic adjustment differed greatly between the contrasting genotypes under water deficit stress, and they were highly correlated to the growth of barley seedlings, suggesting the potential of them to be the selection criteria for drought tolerance. The analysis of the variable importance of these traits in drought tolerance indicated that sap osmolality and relative water content in the youngest fully-expanded leaf are the suitable selection criteria of screening for drought tolerance in barley at seedling stage.